Multimorbidity concept as integrative research method of mental and somatic disorders mechanisms - G. V. Rukavishnikov; E. D. Kasyanov; D. V. Pinakhina; A. O. Kibitov; N. G. Neznanov; G. E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
The problem of the simultaneous history of several diseases, including somatic ones, in one patient is of high relevance in the context of the prevention, diagnosis and treatment of mental disorders. The complexity and multivariance of the relationships of concomitant diseases does not allow us to evaluate their complex interaction according to the concept of comorbidity. The concept of multimorbidity is convenient and promising for studying various aspects of the combination of both mental disorders and their associations with somatic pathology. However, at present, most studies in the area of multimorbidity are based primarily on epidemiological assessments, while much less attention has been paid to the mechanisms of multimorbid conditions. In this review, we consider the main recent approaches related to the study of the multimorbidity of mental disorders and somatic diseases in order to determine the optimal research strategies in this area. Further studies of the etiopathogenetic aspects of multimorbidity, the mechanisms of multimorbid clusters, and the aspects of the course and prognosis of multimorbid diseases are necessary to optimize the concept for both scientific projects and clinical practice. The most important directions for future research on the phenomenon of multimorbidity of mental disorders and somatic diseases are: 1) the study of their shared genetic and molecular mechanisms of development; 2) clinical and fundamental prospective studies of the manifestation, concomitant course and outcomes of multimorbid diseases; 3) study of the effectiveness and tolerability of psychopharmacotherapy in multimorbid patients with various somatic diagnoses, considering the complex interaction of the drugs used.